Enhancing Stability of Thin-Walled Short Steel Channel Using CFRP under Eccentric Compression. (28th September 2016) - Tang, Hongyuan; Wang, Canjun; Wang, Ruijiao
Abstract : This paper presents the experimental and analytical results of eccentrically loaded short cold-formed thin-wall steel channels strengthened with transversely oriented carbon fiber reinforced polymer (CFRP) strips around their web and flange. Seven specimens, each 750 mm long, were fabricated; the main parameters were the number of CFRP plies (one or two) and the space between the CFRP strips (50, 100, or 150 mm). The application of the CFRP strips results in increases in ultimate load capacity and, with the exception of the most heavily reinforced (2 plies at 50 and 100 mm), local buckling was observed prior to global buckling. To extend and better understand the experimental work, a companion analytical study was conducted. Comparisons between experimental observations and computed results show that the analyses provided good correlation to actual behavior. In addition, the numerical results explained the observed phenomenon that flange local buckling was constrained to regions between the CFRP strips.